Influência do desgaste das fresas na adaptação de intermediarios protéticos fresados com sistema CAD/CAM, sobre implantes osseointegrados de hexágono externo - Osorio, Luciane Solange Arevalo (2019)
In the past decades it has been possible to observe CAD/CAM (Computer-Aided Design/ Computer-Aided manufacturing) as a system of great impact within the scope of Odontology. This is made up of three stage: a reading system (scanning) that inspects the structures to be copied, in the mouth or in plaster models; the software (CAD), in which one can make a virtual drawing of the elements necessary for the prosthetic rehabilitation, according to the file attained by the scanner; and the CAM system of milling/printing projects elaborated. One of the benefits of the CAD/CAM system is the excellent marginal adaptation of the milling components, notably in abutments implants. It is known that the tolerable values of disadaptation, considering both conventional prosthetics or over implants, are inferior to 100µm. The factors that interfere in this adaptation range from the correct reading of the substract to appropriate drawing and milling. Overuse of the milling tools can interfere in the final result of the product, having impact on its quality. The identification of the most appropriate moment to change the tools is an important data, considering both the usage and the aspect of the cost of the operational system. This study aims to evaluate the lifespan and impacts of usage of CAD/CAM milling on the implants milled components, having as criteria the analysis of vertical disadaptation. In order to do this, this project will use components sequentially milled, with the continuous use of milling cutters over different substracts, such as Colbalt Chrome (CoCr), Titanium (F136) and Zirconia. The same components will be observed with the help of microscopic optic for quantification of vertical disadjustment, correlating it with the milling cutters wear.